Komponen Bioaktif dan Aktivitas Antioksidan Kerang Balelo (Conomurex sp.) : Bioactive Compound and Antioxidant Activity of Balelo Sea Snail (Conomurex sp.) - Nurhikma; Mirsa; Wulandari, Diah Anggraini (Jurnal Pengolahan Hasil Perikanan Indonesia, 2021)
Molluscs have great potential to developed as a new candidate of antioxidant activity in the pharmaceutical and nutraceutical field. This study aims to investigate the bioactive compound and antioxidant activity of balelo sea snail (Conomurex sp.) from Derawan island, East Kalimantan. Extraction of balelo sea snail was carried out using three types of solvents, such as methanol, ethanol, and ethyl acetate. The analysis method consist of yield analysis, chemical composition, bioactive compounds and antioxidant activity using DPPH. Balelo sea snail had 27.30% of protein content, 2.00% of ash, 10.30% of lipid, and 4.11% of carbohydrate. The yield of balelo sea snail meat was 34.7%, and the yield of methanol, ethanol and ethyl acetate extract were 15.33%, 15.16% and 0.89%, respectively. Balelo sea snail contain alkaloid, tannins, saponins, phenol hydroquinone and steroids. And antioxidants activity of extract methanol and ethanol balelo sea snail (IC50) were 1.055, 8 µg/mL and 1,165.9 µg/mL respectively. Balelo sea snail potential as an antioxidant and has bioactive compound that can be develop in the pharmaceutical and nutraceutical field.